Neuroprotective effects of Tualang honey against oxidative stress and memory decline in young and aged rats exposed to noise stress - Azman, Khairunnuur Fairuz; Zakaria, Rahimah; Othman, Zahiruddin; Aziz, Che Badariah Abdul (Taibah University, Madinah, Kingdom of Saudi Arabia, 2018)
The neuroprotective effects of Tualang honey in stress-induced young and aged rats were investigated. Tualang honey (200 mg/kg body weight) was administered for 28 days. Stressinduced rats were subjected to loud noise 100 dB(A) 4 hours daily for 14 days. Stress exposure significantly induced memory impairment, increased brain oxidation indices, and decreased antioxidant enzymes activities and neuronal density in mPFC, CA2 and CA3 hippocampal areas in both young and aged rats. The stressed rats treated with Tualang honey showed a significant decrease in stress hormone levels and brain oxidation indices, and increase in memory, antioxidant enzymes activities, and neuronal density in mPFC and hippocampus compared to the vehicle-treated stressed rats. The protective effect of Tualang honey was more prominent in young than aged rats. These results suggest the neuroprotective effects of Tualang honey against oxidative stress and memory decline due to stress exposure and/or ageing through its antioxidant property.